PENGARUH LABA KOTOR, LABA OPERASI DAN LABA BERSIH SEBAGAI PREDIKTOR ALIRAN KAS MASA DATANG - Indah Febriani; Erly Sherlita (Jurnal Akuntansi Bisnis dan Ekonomi (JABE), 2022)
This study aims to provide empirical evidence regarding the effect of gross profit, operating profit, and net income on the prediction of future cash flows. This study used quantitative descriptive research method. The sample of this research includes 15 transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2017-2020. The sampling technique used was purposive sampling method. IBM SPSS statistics 25 was used to analyze the data. The results show that gross profit has an effect on prediction of future cash flows, operating profit has an effect on prediction of future cash flows, net income has no effect on prediction of future cash flows, and simultaneously, gross profit, operating profit, and net income have an effect on prediction of future cash flows in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period..